Batasan Rumah Susun Yang Dijadikan Agunan Pada Bank - Bahrudin, Rizal; Hartanto, J. Andy (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
Abstract: This article discusses existence and the authority of certificate executorial of guarantee right to ownership right of apartment as loan collateral in credit agreement in bank. The law of Apartment has become object of collateral which can be burdened with the law of Guarantee Right and can only be subject of ownership right on apartment because it is an independent property. The legal consideration of execution for guarantee right on apartment is stipulated in article 20 of the law, in which object of guarantee right is sold through public auction and certificate holder of guarantee right is entitled to take all or part of the revenue to pay debts with the right before other creditors. The article suggests that when applying the principle of prudence, banks would not be able to channel loan or credit without collateral. Ownership right on apartment may be used as object of credit collateral and bound with guarantee right. Key words: Apartment, collateral, credit